2021
DOI: 10.1002/hep.32174
|View full text |Cite
|
Sign up to set email alerts
|

Generation of neutrophil extracellular traps in patients with acute liver failure is associated with poor outcome

Abstract: Background and Aims: Acute liver failure (ALF) is characterized by significant changes in the hemostatic system and by systemic inflammation. The formation of neutrophil extracellular traps (NETs), in which an activated neutrophil expels its DNA, histones, and granular enzymes, such as myeloperoxidase (MPO), has been associated with immune-mediated and thrombotic diseases. We hypothesized that formation of NETs in patients with ALF contributes to progression of disease. Approach and Results:A total of 676 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…This study by von Meijenfeldt et al provides the first description of the generation of neutrophil extracellular traps (NETs) in 676 patients with ALF and associates NETs with poor outcomes. [ 1 ]…”
Section: Figurementioning
confidence: 99%
“…This study by von Meijenfeldt et al provides the first description of the generation of neutrophil extracellular traps (NETs) in 676 patients with ALF and associates NETs with poor outcomes. [ 1 ]…”
Section: Figurementioning
confidence: 99%
“…Compared with the control group, the level of NETs in the lung tissue increased signi cantly in the model group, and reached the peak at 6-12 h (Figure 4b). MPO is a component of NETs, and its protein expression is highly correlated with the level of NETs [10] . The level of MPO in the lung tissues of mice in the model group was signi cantly increased at 2-12 h after injury, and peaked at 6 h, but there was no signi cant difference between the model group and the control group at 24 h (Figure 4c).…”
Section: The Level Of Nets In Lung Tissuementioning
confidence: 99%
“…PT-INR is regulated by multiple coagulation factors synthesized in the liver and is widely used to monitor anticoagulation, to assess hepatic function, and to evaluate coagulation abnormalities. Previous studies revealed that PT-INR level was closely related to status of inflammation among serious of diseases [ 8 , 9 ]. Similarly, some studies showed a higher PT-INR level was significantly associated mortality in patients undergoing endarterectomy [ 10 ], or with acute heart failure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%